2015
DOI: 10.1002/stem.1907
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 Silencing Enhances In Vitro and In Vivo Osteogenic Differentiation of Human Adipose-Derived Stem Cells by Triggering Activation of BMP-ERK/FGF Signaling and TAZ Upregulation

Abstract: Mesenchymal stem cells (MSCs) show promise for cellular therapy and regenerative medicine. Human adipose tissue-derived stem cells (hASCs) represent an attractive source of seed cells in bone regeneration. How to effectively improve osteogenic differentiation of hASCs in the bone tissue engineering has become a very important question with profound translational implications. Numerous regulatory pathways dominate osteogenic differentiation of hASCs involving transcriptional factors and signaling molecules. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 84 publications
(127 reference statements)
2
40
0
2
Order By: Relevance
“…The ERK signaling pathway is important in osteogenic commitment of various cell types [24,31,32]. In the present study, we demonstrated that Panx3 overexpression enhanced ERK activity.…”
Section: Discussionsupporting
confidence: 63%
“…The ERK signaling pathway is important in osteogenic commitment of various cell types [24,31,32]. In the present study, we demonstrated that Panx3 overexpression enhanced ERK activity.…”
Section: Discussionsupporting
confidence: 63%
“…In turn, cancer cells may express the corresponding markers. Although there is no unique marker for clinical identification, the increase or decrease in the number of a substance in adipose tissue may directly or indirectly reflect the initiation, progression, and invasion of the tumor, such as the EMT-like phenotypic alterations accompanied by the upregulation of matrix metallopeptidase 9 (MMP9) and TWIST1 202, 203. Higher aromatase activity and higher degrees of obesity may abate the efficacy of aromatase inhibitors 204.…”
Section: Adipose Cellsmentioning
confidence: 99%
“…mCT was performed using a high-resolution MicroCAT IIÔ (ImTek, Inc.) small animal imaging system, with previously described settings. 46 Two-dimensional projection images were used to reconstruct tomograms with a commercial software package (Cobra EXXIM; EXXIM Computing Corp.), resulting in a resolution of 80 mm. Three-dimensional reconstructions were generated by MicroView software (GE Healthcare).…”
Section: Micro-computed Tomography Imagingmentioning
confidence: 99%
“…Mineralization of the extracellular matrix was assessed by alizarin red staining and quantification at days 21-28 of the differentiation as previously described. 46 RNA isolation, reverse transcription, and quantitative real time polymerase chain reaction Total RNA isolation, reverse transcription-polymerase chain reaction (RT-PCR), quantitative PCR (qPCR), primers sequence for mouse and human Runx2, Bglap, and Gapdh, and annealing temperature were previously described. 11,13,47 Specific primers for Bmp2 and Smad6 and Id2 were designed based on their GenBank sequence, and sequences are as follows: mSmad6Fwd:TACCACTTCAGCCGGCCTCTG; mSmad6Rev:AGTACGCCACGCTGCACCAGT; mBmp2Fwd: ACCCGCTGTCTTCTAGTGTTG; mBmp2Rev:TCTCTGC TTCAGGCCAAACA; mId2Fwd:GATGATCGTCTTGCCC AGGT; mId2Rev:TCTGGTATTCACGCTCCACC annealing at 57°C.…”
Section: Mouse Tissue Harvesting and Primary Cell Culturementioning
confidence: 99%